2015
DOI: 10.1371/journal.ppat.1004721
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 1 (HTLV-1) Tax Requires CADM1/TSLC1 for Inactivation of the NF-κB Inhibitor A20 and Constitutive NF-κB Signaling

Abstract: Persistent activation of NF-κB by the Human T-cell leukemia virus type 1 (HTLV-1) oncoprotein, Tax, is vital for the development and pathogenesis of adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). K63-linked polyubiquitinated Tax activates the IKK complex in the plasma membrane-associated lipid raft microdomain. Tax also interacts with TAX1BP1 to inactivate the NF-κB negative regulatory ubiquitin-editing A20 enzyme complex. However, the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 76 publications
(106 reference statements)
1
57
0
Order By: Relevance
“…It has been postulated that CADM1 expression is induced by human T-cell leukemia virus 1 (HTLV-1)-encoded gene products such as Tax and HBZ in ATLL. 13,16 But this scenario cannot explain the fact that CADM1 is expressed by S ezary cells without HTLV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that CADM1 expression is induced by human T-cell leukemia virus 1 (HTLV-1)-encoded gene products such as Tax and HBZ in ATLL. 13,16 But this scenario cannot explain the fact that CADM1 is expressed by S ezary cells without HTLV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that the expression of CADM1 is not a simple activation marker, because CD3/CD28 stimulation of normal human lymphocytes induced CD25 and HLA‐DR expression, but did not induce CADM1. It has been postulated that CADM1 expression is induced by human T‐cell leukemia virus 1 (HTLV‐1)‐encoded gene products such as Tax and HBZ in ATLL . But this scenario cannot explain the fact that CADM1 is expressed by Sézary cells without HTLV‐1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…CADM1 (also known as TSLC1, NECL-2, IGSF4, SynCAM1) acts as a tumor suppressor in a variety of human cancers [91,92] and has been proposed as a cell surface marker for ATLL [93]. Pujari et al suggest that Tax-1 may require CADM1 to inactivate negative regulators of NF-κB and maintain persistent NF-κB activation [94]. The same authors demonstrated that CADM1 is upregulated by Tax-1 and associates with Tax-1 in cellular complexes containing Ubc13, TAX1BP1, OPTN, and NEMO in membrane lipid raft microdomains [94,95].…”
Section: Tax-mediated Nf-κb Activationmentioning
confidence: 99%
“…In patients with ATLL , CADM1 expression in combination with CD7 downregulation closely correlates with clonal expansion of leukemic cells (14). Functionally, trans-homophilic interactions of CADM1 activates PI3K (15) and NF-kB (16), whereas trans-heterophilic CADM1 interaction triggers recruitment of the RAC1 GEF, TIAM1, to the CADM1cytoplasmic domain, leading to RAC1 activation and remodeling of actin-network and lamellipodia formation (11). Although RAC1 is known to be required for CADM1 function in ATLL, PAK kinases supporting CADM1-dependent stroma adhesion of ATLL cells have not been defined.…”
Section: Introductionmentioning
confidence: 99%